Wavering between hope and disenchantment: the case of early school leaving in Portugal - Sebastião, J.; Alvares, M. (Scuola democratica, 2015)
The Portuguese education system has undergone a number of very significant changes in recent decades, many of which reflect the attempted recovery of a long history of low levels of schooling. The permanence of the school dropout situations in Portuguese schools at higher levels than the European average shows that mass schooling is yet a recent phenomenon and still subject to questioning by certain parts of the population and political and social elite. This article aims to analyse the evolution of dropout situations putting them in perspective, to try to identify their key characteristics, critical moments and impact of education policy measures.